Determinants of Profitability for Manufacturing Companies in Indonesia 2018-2019 - Liliana Inggrit Wijaya; Jennifer Audrey Harjono; Putu Anom Mahadwartha (Program Studi Akuntansi FPEB UPI, 2022)
Profitability has become one of the most researched topics. However, some of studies have different results. This study is aimed to gain a better understanding of some factors that might have significant effects on profitability. This study examines the influences of internal and external factors on the profitability of companies within the manufacturing sector listed in the Indonesia Stock Exchange (BEI) during 2018-2020. This research utilizes secondary data and a quantitative approach through multiple linear regression. This study includes profitability as dependent variable, with firm size, firm age, liquidity, capital structure, firm growth, capital intensity, and macroeconomic indicator as independent variable. There are 789 observations that used within the study. These observations consisted of 263 companies in 3 years. Firm size, firm age, liquidity, firm growth, capital intensity, and macroeconomic indicator have significant and positive effect on profitability. Capital structure is found to have significant and negative influence on profitability. Keywords. Profitability; Liquidity; Firm Growth; Capital Intensity.